Retrouver le temple du sacré : la logique des extrêmes dans le roman de Durtal - Eléonore Sibourg (Quêtes Littéraires, 2013)
In the late 19th century a reversal of the values linked to the sacred and the profane can be observed. As Religion retreats, Positivism and faith in Progress fill the gap left by the abandoned spiritual belief. A nostalgia for transcendence arises amongst writers. Naturalism turns out to be sterile, but, sill, a belief in God seems to have become impossible. It is in this context that Huysmans writes his novels. The Durtal tetralogy in particular focuses on this theme: desperate, the main character wanders around Catholicism, seeking a sense of the Sacred. He first explores the world of Satanism before the conversion. But even when faith is regained, problems are not solved. In the religious domain itself, Durtal condemns the sacralization of the profane. Henceforth, the Durtal tetralogy manifests itself as a novel of the in-between: from brothel to church, between up-above and down-below, between almighty materialism and bourgeois Catholicism, this misanthropic writer prays for a renewed and primitive form of religious practice in which the individual can access the Sacred again. The quest for the supernatural, through a questioning of contemporary society, becomes a quest for Identity.